Synthesis of CuO nanoparticles using waste-derived bamboo cellulose for enhanced catalytic and antibacterial applications - Zheng, Alvin Lim Teik; Sabidi, Sarah; Maran, Melissa Alexander; Ban, Tan Kar; Seng, Kelly Wong Kai; Chung, Eric Lim Teik; Andou, Yoshito (North Carolina State University, 2025)
Copper oxide (CuO) nanoparticles were prepared using waste-derived cellulose from bamboo biomass as a functional additive. The cellulose, recovered from an alkaline dissolution process, enhanced the dispersion and structural integrity of CuO nanoparticles (NPs). The CuO prepared in the presence of waste cellulose (CuO-C) exhibited a specific surface area of 32 m²/g, compared to 7 m²/g for pure CuO. Scanning electron microscopy (SEM) revealed a feather-like CuO structure influenced by the presence of the waste-derived cellulose matrix. The catalytic activity of CuO-C was tested through the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP), achieving complete conversion within 15 min. The synthesis cost of CuO-C was approximately RM 3.30 per gram. Antibacterial tests confirmed activity against both Staphylococcus aureus and Klebsiella pneumoniae. These findings demonstrate the feasibility of using a highly alkaline solution from the cellulose dissolution process to produce low-cost CuO with improved catalytic and antibacterial properties.